Glycolic acid-g-chitosan-gold nanoflower nanocomposite scaffolds for drug delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This paper reports a simple novel method for the synthesis of flower like gold nanoparticle (three dimensional branched nanoparticle) with >30 tips, under controlled temperature condition. Formation of flower like Au nanoparticle was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and gold nanoflower (AuNF) in controlled drug delivery and tissue engineering applications. The drug loaded novel nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Grafting of glycolic acid to the chitosan and incorporation of drug were evaluated by Fourier transform infrared spectroscopy (FTIR). The nanohybrid scaffolds were found to be stable towards the pH of the medium. The cell viability study shows that prepared nanohybrid scaffolds are biocompatible. Gold nanoflowers were found to control the drug release rate in the buffer solution (pH 7.4). Therefore, for the glycolic acid grafted chitosan based system, gold nanoflowers are the viable additive for drug delivery. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Drug delivery system; Glycolic acid grafting; Gold nanoflower; Nanocomposite